1971
DOI: 10.1172/jci106528
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal fluctuations in triglyceride, free fatty acids, and insulin during sucrose consumption and insulin infusion in man

Abstract: A B S T R A C T Serial changes in circulating triglyceride, free fatty acids (FFA), insulin, and glucose have been measured in human subjects fed sucrose as the sole source of calories for 2-or 3-day periods. The sucrose was given either during the day with overnight fasting (19 subjects) or as continual 3-hour meals during the day and night (seven subjects). Insulin was infused overnight in five additional subjects on the day-feeding regimen to determine the effect on triglyceride concentration.The concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0
1

Year Published

1973
1973
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(20 citation statements)
references
References 27 publications
3
16
0
1
Order By: Relevance
“…In 1969, we reported (6) that carbohydrate induction of hypertriglyceridemia in normal subjects occurs at night and appears to be related to a rebound rise of free fatty acids after diurnal feeding of a high carbohydrate formula diet. This biphasic response of plasma triglycerides to high carbohydrate feeding on a 24 h basis has since been confirmed by Barter, Carroll, and Nestel (7). The present investigation was undertaken in order to study the effect on 24-h triglyceride, free fatty acid, blood sugar, and insulin profiles of inhibition of nocturnal lipolysis by glucose or nicotinic acid.…”
Section: Introductionsupporting
confidence: 62%
“…In 1969, we reported (6) that carbohydrate induction of hypertriglyceridemia in normal subjects occurs at night and appears to be related to a rebound rise of free fatty acids after diurnal feeding of a high carbohydrate formula diet. This biphasic response of plasma triglycerides to high carbohydrate feeding on a 24 h basis has since been confirmed by Barter, Carroll, and Nestel (7). The present investigation was undertaken in order to study the effect on 24-h triglyceride, free fatty acid, blood sugar, and insulin profiles of inhibition of nocturnal lipolysis by glucose or nicotinic acid.…”
Section: Introductionsupporting
confidence: 62%
“…Whether this reflects true circadian control of meal lipid and carbohydrate handling or entrainment to a habitual sequence of meals is not clear. While there is some evidence to suggest circadian variation in postprandial lipid response (Reaven et al, 1988;Romon et al, 1997) and in plasma total TAG concentrations (Barter et al, 1971;Schlierf & Dorow, 1973;Rivera-Coll et al, 1994), the experimental designs of such studies do not exclude the possibility that such observations may reflect the frequency or macronutrient content of the test meals. Fielding et al (1996) and Evans et al (1998) reported appearance of fatty acids in TAG in a chylomicron-rich lipoprotein fraction following the second meal of a two-meal sequence which was suggested to result from incomplete mobilisation from the gut of TAG from the first meal.…”
Section: Discussionmentioning
confidence: 99%
“…But in the work of Barter et al [5] identical fasting periods between meals were designed and lower insulin secretion was observed in men in the afternoon than in the morning.…”
Section: Discussionmentioning
confidence: 99%
“…The known rhythm pattern in glucose and/or insulin values observed in men by several investigators using such stimuli of insulin secretion as meals [3,4,5] oral [1,9,13] or intravenous [13] glucose loads, and tolbutamide [2,13], has not received clear cut explanations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation